Complete and Durable Response in Metastatic Uterine Leiomyosarcoma with Multimodal Therapy: A Case Report - Ajami, Ramin; Moghareabed, Reza; Shekarkhar, Golsa; Mehrtash, Amir Hosein (Archives of Clinical and Medical Case Reports, 2025)
Background: Uterine leiomyosarcoma (LMS) is a rare, aggressive malignancy (1-2% of uterine cancers) [1] often initially misdiagnosed as benign fibroids. There is no reliable preoperative method to distinguish LMS from leiomyoma, and the diagnosis is typically confirmed post-hysterectomy on pathology [1]. LMS frequently metastasises hematogenously (commonly to the lungs, liver, and peritoneum) [1,10], and the prognosis of advanced disease is poor (5-year survival rate is 15- 20%) [1,10]. The standard treatment is total hysterectomy; the benefit of adjuvant therapy remains unclear, although chemotherapy and radiation are often attempted in high-risk cases [7,8]. LMS can express hormone receptors, suggesting a potential benefit of endocrine therapy in select cases [2,5]. Case: We present the case of a 54-year-old woman with a history of a rapidly enlarging “fibroid” who underwent hysterectomy and was found to have high-grade LMS with metastatic spread. The tumour was strongly positive for oestrogen, progesterone, and androgen receptor. Postoperatively, she received pelvic radiation, combined ovarian suppression (goserelin) plus antiandrogen (bicalutamide) hormonal therapy, and targeted kinase inhibitor pazopanib. This regimen was chosen in lieu of conventional chemotherapy, given the tumour’s receptor profile. Outcomes: The patient achieved complete metabolic remission on PET-CT three months after treatment. She has remained disease-free on maintenance therapy with goserelin, bicalutamide, and pazopanib for over 24 months of follow-up, with no evidence of recurrence. Conclusion: This exceptional response in patients with metastatic LMS highlights the potential of an individualised multimodal approach. Exploiting hormone receptor positivity with endocrine therapy and incorporating targeted anti-angiogenic therapy (pazopanib) achieved an outcome rarely observed in advanced LMS. Ongoing surveillance is paramount. This case underscores the importance of multidisciplinary, personalised strategies and encourages further research on hormonetargeted and innovative therapies for uterine LMS.